A single institution report of 19 hepatocellular carcinoma patients with bile duct tumor thrombus - Chotirosniramit, Anon (J Hepatocell Carcinoma, 2017)
BACKGROUND: Obstructive jaundice caused due to bile duct tumor thrombus (BDTT) in a hepatocellular carcinoma (HCC) patient is an uncommon event. This study reports our clinical experiences and evaluates the outcomes of HCC patients with BDTT in a single institution. METHODS: A retrospective review of 19 HCC patients with secondary obstructive jaundice caused due to BDTT during a 15-year period was conducted. RESULTS: At the time of diagnosis, 14 (73.7%) patients had obstructive jaundice. Eighteen (94.7%) patients were preoperatively suspected of “obstruction of the bile duct”. Sixteen patients (84.2%) underwent a hepatectomy with curative intent, while two patients underwent removal of BDTT combined with biliary decompression and another patient received only palliative care as his liver reserve and general condition could not tolerate the primary tumor resection. The overall early recurrence (within 1 year) after hepatectomy occurred in more than half (9/16, 56.3%) of our patients. The 1-year survival rate of patients was 75% (12/16). The longest disease-free survival time was >11 years. CONCLUSION: Identification of HCC patients with obstructive jaundice is clinically important because proper treatment can offer an opportunity for a cure and favorable long-term survival.